2021
DOI: 10.1088/2058-6272/ac23bd
|View full text |Cite
|
Sign up to set email alerts
|

Energy properties and spatial plume profile of ionic liquid ion sources based on an array of porous metal strips

Abstract: An ionic liquid ion source (ILIS) is a kind of high brightness ion source capable of providing high-speed positive or negative ion beams. This paper presents a miniaturized ILIS based on an array of porous metal strips. The porous emitter array, integrated with seven 10 mm long strips, is fabricated using wire electrical discharge machining (WEDM) combined with electrochemical etching. The assembled ILIS is 30 mm×30 mm×17.5 mm in size and weighs less than 25 g. A series of experiments, including an I-V cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In contrast to cone emitters, these emitters will operate at a higher voltage due to only having one radius of curvature at the emission surface. On the other hand, only having curvature in one direction results in a narrow plume in the ridgewise direction of the wedge Liu, Kang, Deng, & Sun, 2021). Additionally, the long emission surface results in a tight collection of emission sites along the wedge without the need for emitter parallelization.…”
Section: Wedge Geometrymentioning
confidence: 99%
“…In contrast to cone emitters, these emitters will operate at a higher voltage due to only having one radius of curvature at the emission surface. On the other hand, only having curvature in one direction results in a narrow plume in the ridgewise direction of the wedge Liu, Kang, Deng, & Sun, 2021). Additionally, the long emission surface results in a tight collection of emission sites along the wedge without the need for emitter parallelization.…”
Section: Wedge Geometrymentioning
confidence: 99%
“…Researchers have conducted experimental and simulation studies to analyze the characteristics and selfneutralization effectiveness of plumes. It has been observed that ILET can operate in a pure ion mode, with monomers and dimers accounting for over 90% of the plume [28][29][30][31]. Courtney et al [16] investigated the coupling effect of temporal and spatial distributions on the self-neutralization of the plume.…”
Section: Introductionmentioning
confidence: 99%
“…1 Schematic of the electrospray thruster potential analyzer (RPA) experiments have shown that variations in initial ion emission energy can influence the spacing between the cation-anion pairs. Past a certain energy threshold, the cation and anion molecules may overcome their attractive Coulomb forces, resulting in ion cluster dissociation or fragmentation of downstream solvated ion clusters [24,25]. Furthermore, Gamero-Castaño [26] implemented an Eulerian electrospray beam model based on the line-of-point-charges approach and demonstrated a strong dependence of charged droplet trajectories on their initial velocities.…”
Section: Introductionmentioning
confidence: 99%